Review of the relationship and underlying mechanisms between the Qinghai–Tibet plateau and host intestinal flora - Lv, Jin; Qi, Ping; Bai, Liu-Hui; Yan, Xiang-Dong; Zhang, Lei (Frontiers in Microbiology, 2022)
The intestinal microbial community is the largest ecosystem in the human body, in which the intestinal flora plays a dominant role and has a wide range of biological functions. However, it is vulnerable to a variety of factors, and exposure to extreme environments at high altitudes, as seen on the Qinghai–Tibet plateau, may cause changes in the structure and function of the host intestinal flora. Conversely, the intestinal flora can help the host adapt to the plateau environment through a variety of ways. Herein, we review the relationship and underlying mechanism between the host intestinal flora and the plateau environment by discussing the characteristics of the plateau environment, its influence on the intestinal flora, and the important role of the intestinal flora in host adaptation to the plateau environment. This review aimed to provide a reference for maintaining the health of the plateau population.